The accuracy of anthropometric indices in detecting hypertension in Sudanese adults: a cross-sectional study - Imad R. Musa; Osman E. Osman; Ahmed M. Khair; Ishag Adam (BMC Public Health)
Abstract Background Hypertension is an increasing health problem; hence, efforts have been made to promote the disease's early detection and modify prognoses. We aim to evaluate the accuracy of body mass index (BMI), waist circumference (WC), and waist-height ratio (WHtR) in detecting hypertension among adults in Northern Sudan. Methods Adults were recruited for a multi-stage sampling survey in Northern Sudan. Sociodemographic and anthropometric index (BMI, WC, and WHtR) information were collected. A receiver operating characteristic (ROC) curve with its area under the curve (AUC) was obtained, and a multivariate binary analysis was performed. Results Of the 301 included adults, 113 (37.5%) were females and 188 (62.5%) were males. The median (interquartile range, IQR) age was 45.0 (32.0‒59.0) years. The median (IQR) of BMI, WC, and WHtR was 25.6 (21.9‒29.7) kg/m2, 83.0 (73.0‒94.8) cm, and 0.51 (0.43‒0.58), respectively; these values were significantly higher in adults with hypertension compared with adults without hypertension. A total of 166 (55.1%) adults had hypertension. BMI (AUC = 0.69 at the cutoff 22.5 kg/m2, sensitivity = 0.89, specificity = 0.53, YI = 0.35) and WHtR for both males and females (AUC = 0.68 at the cutoff 0.48, sensitivity = 0.75, specificity = 0.60, YI = 0.35) were more accurate than WC (AUC = 0.66 at the cutoff 77.5 cm, sensitivity = 0. 77, specificity = 0.56, YI = 0.33). The multivariate binary analysis revealed that being female (adjusted odds ratio [AOR] = 2.23, 95.0% CI = 1.25‒3.97), having increased age (AOR = 1.04, 95% CI = 1.02‒1.05), and having a higher BMI (AOR = 1.10, 95% CI = 1.04‒1.16) were associated with hypertension. Conclusion BMI, WC, and WHtR showed moderate predictive power, suggesting that these indices have a limited role in diagnosing hypertension at the individual level and are more appropriate for population screening than for individual diagnosis. BMI performs better than WC in terms of hypertension detection.